Mucosal Immunogenicity of a Holotoxin-Like Molecule Containing the Serine-Rich Entamoeba histolytica Protein (SREHP) Fused to the A(2) Domain of Cholera Toxin - Sultan, Faisal (American Society for Microbiology, 1998)
One strategy for the induction of mucosal immune responses by oral immunization is to administer the antigen in conjunction with cholera toxin. Cholera toxin consists of one A polypeptide (CTA) which is noncovalently linked to five B subunits (CTB) via the A(2) portion of the A subunit (CTA(2)). Coupling of antigens to the nontoxic B subunit of cholera toxin may improve the immunogenicity of antigens by targeting them to GM1 ganglioside on M cells and intestinal epithelial cells. Here, we describe the construction of a translational fusion protein containing the serine-rich Entamoeba histolytica protein (SREHP), a protective amebic antigen, fused to a maltose binding protein (MBP) and to CTA(2). When coexpressed in Escherichia coli with the CTB gene, these proteins assembled into a holotoxin-like chimera containing MBP-SREHP-CTA(2) and CTB. This holotoxin-like chimera (SREHP-H) inhibited the binding of cholera toxin to GM1 ganglioside. Oral vaccination of mice with SREHP-H induced mucosal immunoglobulin A (IgA) and serum IgG antiamebic antibodies and low levels of mucosal anti-CTB antibodies. Our studies confirm that the genetic coupling of antigens to CTA(2) and their coexpression in E. coli can produce holotoxin-like molecules that are mucosally immunogenic without the requirement for supplemental cholera toxin, and they establish the SREHP-H protein as a candidate for evaluation as a vaccine to prevent amebiasis.